PENGELOLAAN BANTUAN EKONOMI BAGI ANAK YATIM MELALUI PROGRAM KANTOR URUSAN AGAMA DI KECAMATAN JONGKONG KABUPATEN KAPUAS HULU - Arif Fahrudin; Vera Susanti (BORJUIS: JURNAL OF ECONOMY, 2023)
This research is motivated by realizing ourselves as caliphs of Allah, in fact there is not a single human being in this world who does not have a "position" or "position". Other worldly positions are actually an elaboration of the main position as khalifatullah. If someone realizes that his worldly position is an elaboration of his position as khalifatullah, then no human being will misuse his position. So that no one person will commit any deviations while he is in office. Man's position as caliph is a mandate from Allah. Worldly positions, for example those given by our superiors, or those given by fellow humans, are a mandate from Allah, because they are the description of khalifatullah. Objective: This research is to determine the management of economic assistance for orphans through the Religious Affairs Office program in Jongkong District, Kapuas Hulu Regency. Method: This research was conducted using a qualitative descriptive method with an inductive approach. Data sources used in this research include informants, researchers, and documents related to the research object. Data collection techniques used moderate participant observation, semi-structured interviews and documentation. Management of aid for orphans at the Jongkong District Religious Affairs Office (KUA) consists of three processes, namely: planning, direction and supervision. Planning includes systems, open management, clear work plans, publication, and continuous improvement, while in direction, everything is always discussed first, so that what we do is in line with the goals that have been set. The Office of Religious Affairs (KUA) always holds evaluation meetings with the aim of finding out the problems experienced by the management both in collecting aid funds and in distributing aid funds. In supervision, the policies taken by the head of the Office of Religious Affairs (KUA) regarding the management of the orphan aid program are always properly supervised, which means that as head of the management, he always monitors or supervises the progress of aid for orphans until the aid reaches the goal of the aid program, welfare for the people. orphans.